A daily Azores–Iceland North Atlantic Oscillation index back to 1850. (27th March 2015) - Cropper, Thomas; Hanna, Edward; Valente, Maria Antónia; Jónsson, Trausti
<x xml:space="preserve">Abstract</x> We present the construction of a continuous, daily (09:00 UTC), station‐based (Azores–Iceland) North Atlantic Oscillation (NAO) Index back to 1871 which is extended back to 1850 with additional daily mean data. The constructed index more than doubles the length of previously existing, widely available, daily NAO time series. The index is created using entirely observational sea‐level pressure (SLP) data from Iceland and 73.5% of observational SLP data from the Azores – the remainder being filled in via reanalysis (Twentieth Century Reanalysis Project and European Mean Sea Level Pressure) SLP data. Icelandic data are taken from the Southwest Iceland pressure series. We construct and document a new Ponta Delgada SLP time series based on recently digitized and newly available data that extend back to 1872. The Ponta Delgada time series is created by splicing together several fractured records (from Ponta Delgada, Lajes, and Santa Maria) and filling in the major gaps (pre‐1872, 1888–1905, and 1940–1941) and occasional days (145) with reanalysis data. Further homogeneity corrections are applied to the Azores record, and the daily (09:00 UTC) NAO index is then calculated. The resulting index, with its extended temporal length and daily resolution, is the first reconstruction of daily NAO back into the 19th Century and therefore is useful for researchers across multiple disciplines.